Comparison of a New Medicinal Plant Extract and Triamcinolone Acetonide in Treatment of Recurrent Aphthous Stomatitis - Unur M.; Ofluoglu D.; Koray M.; Mumcu G.; Onal A.E; Tanyeri H. (Balkan Stomatological Society, 2014)
The aim of this study was to evaluate the effectiveness of a new medicinal plant extract (Ankaferd Blood Stopper®, ABS) on the healing process of aphthous ulcers. A total of 50 patients with recurrent aphthous stomatitis (RAS) who have had currently a single oral ulcer in the mouth were included in the study. Patients were randomly divided in 2 groups: ABS group and Kenacort group (triamcinolone acetonid). Data were collected by questionnaire regarding age, gender, RAS history including the number of ulcer episodes in 1 month, the number of ulcers in each episode, mean healing time of previous ulcers and the mean disease duration. Ulcer size, ulcer related pain, evaluated by VAS and effectiveness index (EI), was noted in each clinical examination.